2014
DOI: 10.1097/ccm.0000000000000527
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms and Acute Care Service Utilization Over the Course of the Year Following Medical-Surgical ICU Admission

Abstract: Objective To determine if the presence of in-hospital substantial acute stress symptoms, as well as substantial depressive or posttraumatic stress disorder (PTSD) symptoms at 3-months post-intensive care unit (ICU), are associated with increased acute care service utilization over the course of the year following medical-surgical ICU admission. Design Longitudinal cohort study. Setting Academic medical center. Patients 150 patients ≥ 18 years old admitted to medical-surgical ICUs for over 24 hours. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 41 publications
2
28
0
2
Order By: Relevance
“…Comini et al 20 found that, despite notable improvement in physical function, there was no change in perceived quality of life or self-efficacy in the first 6 months post-hospital discharge. Consistent with reports from previous studies, [21][22][23] these findings suggest that the impact of critical illness persists for an extended period of time and even after recovering physical independence, distress from remaining physical symptoms (eg, fatigue) may still be present. 19 Because of profound deconditioning after critical illness, it is easy to focus on attempting to restore physical function.…”
supporting
confidence: 81%
“…Comini et al 20 found that, despite notable improvement in physical function, there was no change in perceived quality of life or self-efficacy in the first 6 months post-hospital discharge. Consistent with reports from previous studies, [21][22][23] these findings suggest that the impact of critical illness persists for an extended period of time and even after recovering physical independence, distress from remaining physical symptoms (eg, fatigue) may still be present. 19 Because of profound deconditioning after critical illness, it is easy to focus on attempting to restore physical function.…”
supporting
confidence: 81%
“…In addition, we identified trends that suggested worsening of depressive symptoms when ICU survivors failed to return home during the 4-month post-discharge period and worsening of depressive symptoms and anxiety when care needs were moderate or high. Although psychological symptoms are known to be prevalent in ICU survivors, 11 few studies have described the relationship between psychological symptoms and recovery following critical illness. Because of the descriptive nature of our study, it is not possible to determine if the presence of depressive symptoms and anxiety were factors delaying recovery or a response to this delay.…”
Section: Discussionmentioning
confidence: 99%
“…3 In 150 patients followed for one year after ICU admission for at least 24 hours, unresolved depressive symptoms were associated with an increase in hospital readmissions and emergency department visits. 11 In addition, ICU survivors have reported significant anxiety, with a reported prevalence of 23–41% that can persist for years after ICU discharge. 1217 …”
Section: Introductionmentioning
confidence: 99%
“…Sowohl auf einer Symptomals auch auf einer Störungsebene zeichnet sich für diese affektive Morbidität eine oft langwierige Persistenz ab. Diese wird in einigen prospektiven Longitudinalstudien mit sukzessiven Messzeitpunkten für die ersten Monate nach überstandener intensivpflichtiger Erkrankung [4,5] bis zu 1 und 2 Jahren im weiteren Verlauf [6][7][8], in einigen Follow-up-Studien auch über einen sehr viel längeren Zeitraum nachgewiesen [9,10].…”
Section: Prävalenz/inzidenzunclassified
“…Umgekehrt beeinflussen letztere das allgemeine Krankheitsverhalten und die persönliche Krankheitsverarbeitung negativ und bedingen zusätzlich auch eine intensivere Inanspruchnahme medizinischer Einrichtungen im poststationären Verlauf [6,7,34]. In prospektiven Longitudinalstudien kündigten Besserungen zuvor bestehender körperlicher Beeinträchtigungen auch eine höhere Wahrscheinlichkeit einer Remission von depressiven, Angst-und posttraumatischen Symptomen zum jeweils nachfolgenden Messzeitpunkt an [8].…”
Section: » Körperliche Funktionseinbußen Verstärken Depressive Verstiunclassified